Tobrilus saprophagus sp. n. and Epitobrilus interstitialis sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia - Naumova, Tatyana V.; Gagarin, Vladimir G. (Zootaxa, 2017)
Two new nematode species found in Lake Baikal (Russia) are described and illustrated. Tobrilus saprophagus sp. n. is morphologically close to T. bekmanae Tsalolikhin, 1975 and T. securus Gagarin & Naumova, 2011. The new species differs from T. bekmanae by the less slender tail (♂ cʹ = 2.9–3.9, ♀ cʹ = 3.5–6.8 vs ♂ cʹ = 6, ♀ cʹ = 9 in T. bekmanae), narrower labial region (24–30 µm vs 35–38 µm in T. bekmanae), shorter outer labial setae (10–12 µm vs 13–18 µm in T. bekmanae) and shorter stoma (25–32 µm vs 40–56 µm in T. bekmanae). T. saprophagus sp. n. differs from T. securus by the shorter and less slender tail (♂ c = 11.5–16.1, cʹ = 2.9–3.9, ♀ c = 8.8–13.1, cʹ = 3.5–6.8 vs ♂ c = 6.7–8.4, cʹ = 6.3–9.3, ♀ c = 7.1–8.4, cʹ = 6.6–7.7 in T. securus), longer outer labial setae (10–12 µm vs 6.5–9.0 µm in T. securus) and shorter spicules (45–48 µm vs 52–58 µm in T. securus). Epitobrilus interstitialis sp. n. is close to E. steineri (Micoletzky, 1925), but differs by the longer body (3.88–5.97 mm vs 2.14–3.35 mm), longer tail (250–335 µm vs 160–199 µm for males), longer outer labial setae (27–40 µm vs 22–25 µm) and longer spicules (73–78 µm vs 51–71 µm). Diagnostic morphological characters of males of valid species of the genus Epitobrilus Tsalolikhin, 1981 are given. Tobrilus (Epitobrilus) medius G. Schneider, 1916 (apud Tsalolikhin, 1980) is synonymized with the species Eutobrilus peregrinator Tsalolikhin, 1983.